2015
DOI: 10.1080/01635581.2015.1075560
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Randomized Trial of Lycopene-Rich Tomato Extract Among Men with High-Grade Prostatic Intraepithelial Neoplasia

Abstract: Background A diverse body of evidence suggests that lycopene might inhibit prostate cancer development. We conducted a 6-month repeat biopsy randomized trial among men with HGPIN. Here we report results for serum lycopene, PSA and IGF proteins, histopathological review, and tissue markers for proliferation (MCM-2) and cell cycle inhibition (p27). Methods Participants consumed placebo or tomato extract capsules containing 30 mg/day lycopene. Pre- and post-treatment biopsies were immunostained and digitally sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 38 publications
3
39
0
3
Order By: Relevance
“…Schwenke and coworkers, on the contrary, showed stable PSA levels in hormone refractory prostate cancer patients, and no clinical improvement was reported (15-mg/day lycopene; Schwenke, Ubrig, Thürmann, Eggersmann, & Roth, 2009). These results were confirmed by other studies: 30 mg/day dosage did not modify PSA (Bunker et al, 2007;Gann et al, 2015) and had no effect in androgen-independent prostate cancer patients (Jatoi et al, 2007). Similar results were also obtained by Mariani et al in high-grade prostatic intraepithelial neoplasia patients with 25-mg/day administration (Mariani et al, 2014).…”
Section: Terpenessupporting
confidence: 86%
“…Schwenke and coworkers, on the contrary, showed stable PSA levels in hormone refractory prostate cancer patients, and no clinical improvement was reported (15-mg/day lycopene; Schwenke, Ubrig, Thürmann, Eggersmann, & Roth, 2009). These results were confirmed by other studies: 30 mg/day dosage did not modify PSA (Bunker et al, 2007;Gann et al, 2015) and had no effect in androgen-independent prostate cancer patients (Jatoi et al, 2007). Similar results were also obtained by Mariani et al in high-grade prostatic intraepithelial neoplasia patients with 25-mg/day administration (Mariani et al, 2014).…”
Section: Terpenessupporting
confidence: 86%
“…The ProDiet dietary lycopene intervention equates to tomato consumption previously associated with a reduced prostate cancer risk in ProtecT trial participants (36). However, a small placebo-controlled trial of lycopene supplementation in men with HGPIN showed no differences in expression of tissue markers for proliferation or cell-cycle inhibition (MCM-2 and p27, primary endpoints), PSA or cancer rates on rebiopsy at 6 months (37). Lycopene has cardiovascular benefits although not through lowering blood pressure so different endpoints would be needed in a definitive trial to measure its broader impacts (38).…”
Section: Discussionmentioning
confidence: 99%
“…Mini-chromosome maintenance protein complex (MCM) is a eukaryotic DNA helicase complex required for initiation of DNA replication. The MCM proteins include six members, MCM2 to MCM7, and are considered as molecular markers of proliferation in several types of cancer (3)(4)(5)(6). MCM7 is a critical component of DNA replication licensing complex, and is overexpressed in multiple human malignancies including hepatocellular carcinoma, head and neck squamous cell carcinoma, prostate carcinoma and esophageal squamous cell carcinoma (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%